(untitled) (مجلة جامعة سرت للعلوم الانسانية, 2024)
This research is set to investigate the environmental awareness among postgraduate students at the University of Sirte. This is due to the fact that raising the environmental awareness among students at various stages of education has become so essential due to the multiple problems the environment faces because of human actions. To do so, the research employed a descriptive approach, through reviewing various references and sources as well as previous studies related to this topic of the study. The present researcher’s also used the analytical method in order to analyze the data which was collected through a research instrument developed by the researcher in order to measure the environmental awareness among the students’ participants. The study participants were 130 male and female postgraduate students from the Faculty of Arts and Law and who were in the diploma and writing-up stage in the academic year 2022-2023. The study findings suggested that the participant were interested and motivated in doing research on topics related to environment. The results also highlighted the urgent need to reactivate the national program for environmental education in Libya. Moreover, the results indicated need for exploiting all the available resources of the green and clean energies in the country. In addition, the findings suggest the need for various media programs in raising the environmental awareness for all members of society. The results also showed that the media department in the university should be playing a major educational role in raising the awareness of the environment among university students and all members of the local community.